ADMINISTRATIVE ACTIVITY OF AMIR TEMUR IN THE EYES OF WORLD HISTORIANS - Khalilov M.Sh. (Scholars Digest Publishing, 2023)
This article provides information about the great general Amir Temur's military activities, military campaigns and works left in history. The views and opinions of world historians on Amir Temur's activities are also covered.
Keywords: Sahibqiron, great commander, ruler, victory, military commander, military art, tactics, strategy.